2.8 Ogun, the car god, and the others. Localized practices of power and the perception of health among Nigerian women in prostitution in Italy - Roberta Pompili (AM. Rivista della Società Italiana di Antropologia Medica, 2004)
2.8 Ogun, the car god, and the others.Localized practices of power and the perception of health among Nigerian women in prostitution in Italy